Pendidikan Multikultural Perfektif Filsafat Pendidikan Islam - Nanda Rahayu Agustia; Salminawati; Usiono (At Turots: Jurnal Pendidikan Islam, 2023)
The purpose of this paper is to explain that in the framework of Islamic thought, education is not only a transfer of knowledge, but also a process of moral formation and strengthening of human nature. Multicultural education from the perspective of Islamic education philosophy prioritizes the concept of equality, justice, and respect for all God's creatures regardless of differences in cultural or ethnic backgrounds. The Qur'an and Hadith emphasize the importance of recognizing diversity and appreciating differences as one of the signs of God's greatness. Multicultural education in the Islamic context is not only about recognizing diversity, but also about understanding and practicing the universal values taught by Islam, such as tolerance, cooperation, and mutual respect. Through multicultural education based on Islamic education philosophy, it is expected to build a generation that is not only intellectually intelligent, but also has social awareness, empathy and respect for the diversity that exists in society. This is in line with the goal of Islamic education to create a balanced person in intellectual, spiritual and social aspects.